Controle de temperatura no processamento do café solúvel: reduzindo a formação de acrilamida - Salazar, Guilherme Maruski (Universidade Federal de São Carlos, 2024)
The formation of acrylamide during food processing is a highly relevant topic for food safety, especially in coffee, one of the most consumed beverages worldwide and of great importance to the Brazilian economy. This compound is primarily formed during roasting through the Maillard reaction and has been associated with potential health risks, such as carcinogenic and neurotoxic properties. Thus, the central theme of this study was to analyze the factors related to the formation of acrylamide during coffee processing stages, such as roasting and drying, as well as to evaluate technological strategies to minimize its occurrence without compromising the sensory characteristics of the beverage. This study aims to contribute to the production of safe, high-quality coffee, meeting global market demands and consumer expectations. To achieve this, a methodology based on a literature review of scientific articles, documentary analysis of food safety standards, and evaluation of acrylamide control methods in coffee was used, with an emphasis on identifying gaps and proposing improvements in industrial processes. The literature shows that strict temperature control, especially during the roasting and drying stages, is essential to reduce the formation of acrylamide, a carcinogenic compound. Strategies such as more intense roasting have proven effective in mitigating this substance without compromising the sensory characteristics of the beverage. However, significant gaps were identified, such as the lack of studies on variations in drying temperatures, on the storage conditions of the beans, and the impacts of different types of coffee on acrylamide formation. Thus, it is concluded that the lack of research on new technologies to control this compound at all stages of the process indicates the need for further investigation. Moreover, the creation of clear regulations in Brazil, aligned with international standards, is also essential to ensure the safety and quality of coffee, meeting global requirements.
Temperature control in instant coffee processing: reducing acrylamide formation
Keywords: Torrefação; Coffea arabica; Coffea robusta; Roasting; Arabica coffee; Robusta coffee; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::ENGENHARIA DE ALIMENTOS